(3GdYdGbI Hjf QFjS GdLeghQjI h eLdS GdfhGH aj OSJhQ GdLeghQjI GdjefjI (B: s (3OQGSI ebGQfI (B/ s - (3eMehO MSjf Ydj fGLjs; (3KQhJ HOhj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2014)
(3JCJj CgejI GdehVhY ef fGMjJjf(B: (3GdChdi fXQjI(B: (3hGdCNQi YdejI(B. (3GdCgejI GdfXQjI(B: (3JHQR GdCgejI GdfXQjI dgPG GdHMK aj TQM hJMdjd eLed GdfUhU GdOSJhQjI GdJj JhVM GdYdGbI Hjf QFjS GdLeghQjI heLdS GdfhGH(B: (3haj JhVjM GdWQjbI GdJj jeGQS GdTYH ef NdGdgG GdSjGOI aj GfJNGH gPg GdSdWGJ(B: (3hcPdc eYQaI eG EPG cGf GdeTQY Gdjefj ehabkG aj JMOjO gPg GdYdGbI(B: (3Ce Cf gfGc bUhQkG ef bHd GdeTQY aj gPg GdYdGbI(B: (3eeG LYd EMOi gPg GdSdWGJ Jahb HbjI GdSdWGJ GdCNQi(B. (3GdCgejI GdYdejI(B: (3jecf GSJYQGV GdCgejI GdYdejI ef NdGd HjGf GdhVY GdOSJhQj ddSdWJjf GdJfajPjI hGdJTQjYjI(B: (3MjK jLQj HjGf eG EPG cGf jJe GNJjGQ GdHQdeGf ef bHd GdTYH(B: (3Ce Cf dQFjS GdLeghQjI SdWI JYjjf cd Ch HYV CYVGFg(B: (3hcPdc eOi SdWJg aj EfgGA hdGjJge Yf GdTYH bHd GdCLd GdeMOO dhdGjJge(B: (3hgh eG jYQa HMb GdMd(B. (3cPdc Jcef GdCgejI aj HjGf GdELQGAGJ GdJj jJHYgG GdHQdeGf aj eeGQSJg dSdWGJg(B: (3haj HjGf OhQ QFjS GdOhdI aj GdJCKjQ Ydi OhQGJ GdGfYbGO haj hba LdSGJ GdeLdS(B: (3hWdH GfYbGOg aj ZjQ GdecGf GdeNUU dg ddGfYbGO(B: (3haj HjGf SdWJg aj GbJQGM GdbhGfjf hGdGYJQGV YdjgG hEUOGQgG hfTQgG(B: (3cPdc HjGf eG SjSge Hg OhQ cd ef QFjS GdLeghQjI heLdS GdfhGH aj JWhjQ GdYedjI GdOjebQGWjI hGdYed Ydi JWhjQgGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2014s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B572-603s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3OSJhQ GdLeghQjI GdjefjIs; (3QFjS GdLeghQjI s; (3eLdS GdfhGH s; (3ELQGAGJ GdJQTjM s; (3GdNdGa Gdabgj s; (3GdGYJPGQ Ydi GdbhGfjfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes